2015
DOI: 10.1007/s12039-015-0847-5
|View full text |Cite
|
Sign up to set email alerts
|

Textural and morphological studies of transition metal doped SBA-15 by co-condensation method

Abstract: The 3d transition metals were incorporated into SBA-15 matrix by co-condensation synthesis method. Very low concentrations of metals were introduced into silica framework by maintaining the metal to silica ratio in the synthesis gel at 0.01. The difference in hydrolysis rates of metal and silica precursors have led to textural modifications while demonstrating the structural integrity akin to pristine SBA-15. The physicochemical properties obtained offer some insights into the P123 micelle aggregation and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…An important characteristic presented by this group were that the values of micropore surface area and volume displayed average increases of 146% and 119%, respectively, when compared to pure silica. Charan and Rao [ 39 ] also reported that the insertion of heteroatoms by co-condensation may alter the amount of micropores in SBA-15 samples. This would occur because the presence of the metals changes the energy of the surfactant-solution interface, since the metals compete with silica in the S 0 H + X − I + mechanism (S 0 H + being the surfactant hydrogen bonded to a hydronium ion, X − the chloride ion and I + the protonated inorganic species) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important characteristic presented by this group were that the values of micropore surface area and volume displayed average increases of 146% and 119%, respectively, when compared to pure silica. Charan and Rao [ 39 ] also reported that the insertion of heteroatoms by co-condensation may alter the amount of micropores in SBA-15 samples. This would occur because the presence of the metals changes the energy of the surfactant-solution interface, since the metals compete with silica in the S 0 H + X − I + mechanism (S 0 H + being the surfactant hydrogen bonded to a hydronium ion, X − the chloride ion and I + the protonated inorganic species) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The investigation regarding the isomorphic substitution of heteroatoms into the framework of silica continued through FTIR analyses. The objective was to observe if there were disturbances in the network of silica caused by the presence of foreign atoms by tracking the Si–O–Si bonds around 1060 cm −1 [ 39 , 48 , 49 ]. The maxima of the peaks associated to these bonds in functionalized samples experienced deviations around the value observed for PSi, which are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With an increasing Cr content, the intensity of the (1 0 0) peak decreases as a result of a partial blocking of the SBA-15 mesopores and the deterioration of the ordered pore structure [32]. All the materials exhibit significant changes from the d-spacing of the (1 0 0) plane to lower values in relation to the SBA-15 material, implying dilation in the framework lattice [37]. It is important to take into consideration that there is a decrease in the unit cell constant (a 0 ) and the wall thickness (e) in these materials (Table 1).…”
Section: X-ray Diffractionmentioning
confidence: 98%
“…The appearance of mesostructure characteristics, as attested by low-angle XRD, N 2 adsorption–desorption isotherms, and transmission electron microscopy (TEM), demonstrated the successful synthesis of SBA-15 using a silica originator extracted from POFA. According to the current literature, used for comparative purposes, SBA-15 synthesized from tetraethyl ortho silicate (TEOS) had the largest surface area (699 m 2 /g) [ 86 ], trailed by sodium silicate SBA catalyst with 332 m 2 /g [ 87 ] and POFA-rich silicate with 330 m 2 /g. It was noted that the surface area of the SBA-15 synthesized using POFA sodium silicate was similar to that of commercial sodium silicate.…”
Section: Waste-to-resource Potential Of Pocmentioning
confidence: 99%